Discrimination of tonal and atonal music in congenital amusia: The advantage of implicit tasks. (May 2016) - Tillmann, Barbara; Lalitte, Philippe; Albouy, Philippe; Caclin, Anne; Bigand, Emmanuel
Abstract: Congenital amusia is a neurodevelopmental disorder of music perception and production, which has been attributed to a major deficit in pitch processing. While most studies and diagnosis tests have used explicit investigation methods, recent studies using implicit investigation approaches have revealed some unimpaired pitch structure processing in congenital amusia. The present study investigated amusic individuals' processing of tonal structures (e.g., musical structures respecting the Western tonal system) via three different questions. Amusic participants and their matched controls judged tonal versions (original musical excerpts) and atonal versions (with manipulated pitch content to remove tonal structures) of 12 musical pieces. For each piece, participants answered three questions that required judgments from different perspectives: an explicit structural one, a personal, emotional one and a more social one (judging the perception of others). Results revealed that amusic individuals' judgments differed between tonal and atonal versions. However, the question type influenced the extent of the revealed structure processing: while amusic individuals were impaired for the question requiring explicit structural judgments, they performed as well as their matched controls for the two other questions. Together with other recent studies, these findings suggest that congenital amusia might be related to a disorder of the conscious access to music processing rather than music processing per se. Highlights: We investigated tonal structure processing in congenital amusia. Participants rated tonal musical pieces and atonal versions with 3 questions. Amusics were impaired for explicit structural judgments. Implicit judgments revealed preserved tonal structure processing in amusics. Data suggest amusia as a disorder of conscious access to music processing.